Productivity, morphogenetic and structural characteristics of Xaraés-Brachiaria and Mineirão-Stylo (Research, Society and Development, 2021)
Productivity, morphogenetic and structural characteristics of Brachiaria brizantha cv. Xaraés and Stylosanthes guianensis var. vulgaris cv. Mineirão were evaluated at the Federal University of Jataí. A complete randomized block design was used with two planting arrangements (Xaraés and Estilosantes singles and intercropped) associated with three phosphorus (P) levels (70, 105 and 140 kg/ha P2O5) applied at sowing, with four replications. Data analysis was carried out in a split plot design considering the effect of planting arrangement, block and evaluation period in the plot and the effect of dose and the interaction between planting arrangement and dose as subplot. The mean comparison test was performed by t test at 5% of probability. The 70 kg/ha P2O5 dose used in pasture establishment was adequate to allow proper development for both forages, ensuring its establishment in single and intercropped planting arrangement when the P in the soil is medium. The Brachiaria brizantha cv. Xaraés intercropped with Mineirão had a higher dry matter yield than when it was single and fertilized with 50 kg N/ha.